2019
DOI: 10.1111/evo.13815
|View full text |Cite
|
Sign up to set email alerts
|

Head‐turning morphologies: Evolution of shape diversity in the mammalian atlas–axis complex

Abstract: Mammals flex, extend, and rotate their spines as they perform behaviors critical for survival, such as foraging, consuming prey, locomoting, and interacting with conspecifics or predators. The atlas–axis complex is a mammalian innovation that allows precise head movements during these behaviors. Although morphological variation in other vertebral regions has been linked to ecological differences in mammals, less is known about morphological specialization in the cervical vertebrae, which are developmentally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
4
10
0
Order By: Relevance
“…In particular, the atlas, or first cervical vertebra, acts as the main interface between the head and the axial skeleton and, therefore, plays a critical role in directing and stabilizing head movements (rev. in 4,5 ). As such, previous studies have emphasized the functional link between the morphology of the atlas, head mobility, and postural and locomotor repertoires in catarrhines (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the atlas, or first cervical vertebra, acts as the main interface between the head and the axial skeleton and, therefore, plays a critical role in directing and stabilizing head movements (rev. in 4,5 ). As such, previous studies have emphasized the functional link between the morphology of the atlas, head mobility, and postural and locomotor repertoires in catarrhines (e.g.…”
mentioning
confidence: 99%
“…As such, previous studies have emphasized the functional link between the morphology of the atlas, head mobility, and postural and locomotor repertoires in catarrhines (e.g. [5][6][7] ). More specifically, while the shape and curvature of the articular facets at the atlanto-occipital joint determines the range of head motions in terms of flexion and extension, the atlanto-axial joint is responsible for lateral rotation of the atlas and the head (rev.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, evolution toward more elongate bodies must occur through reduction of body depth, elongation of the head, and/or elongation of the individual vertebrae. Previous work has shown that changes in vertebral shape can generate diverse body shapes from longnecked giraffes with elongate cervical vertebrae to fusiform dolphins with shortened and fused cervical vertebrae (Buchholtz 2001;Buchholtz and Schur 2004;Arnold et al 2017;Vander Linden et al 2019). Furthermore, more recent work has investigated the evolutionary processes that led to increase in the complexity and regionalization of the mammalian vertebral column (Jones et al 2018a, b;Jones et al 2019).…”
mentioning
confidence: 99%
“…2017; Vander Linden et al. 2019). Furthermore, more recent work has investigated the evolutionary processes that led to increase in the complexity and regionalization of the mammalian vertebral column (Jones et al.…”
mentioning
confidence: 99%